THE IMPACT OF SERIAL KILLER MOVIE ON MIDDLE SCHOOL STUDENTS: READER RESPONSE POINT OF VIEW - Haryo Prawiro; Andi Julian; Ali Mustofa (Universitas Negeri Surabaya, 2023)
Serial killer movies have positively and negatively influenced children's behavior, attitude, and perception. This study was conducted on students of middle school in Indonesia. The data was collected through interviews with six Indonesian junior high school children after they watched serial killer movies. The sample was chosen purposively based on the purpose of the study. The study finds out that serial killer movies negatively impact children's psychology, attitudes, and behavior, specifically who watch serial killer movies than other children who do not. After analyzing six participants, the researchers find out that most of the participants feel the same way. Most of them felt terrified and freaking out during the film was played. And above that, most participants do not feel affected psychologically, mentally, emotionally, or spiritually affected them. Some of them have the same shadows as The Joker had, some of them have the same persona as what The Joker had, and some of them have the same animus or feminine side of them as what The Joker had. But that things (Shadow, Persona and Animus) did not affect them psychologically, mentally, emotionally, and spiritually.